(untitled) (ModaPalavra e-periódico, 2021)
Traditionally, around the table adorned with a towel, the family gathers for meals and build emotional moments. From these moments, affective memory holds images, flavors and smells, which survive time and table cloths are responsible for these references. In this sense, the objective of this research was to identify the performance of the elements of emotional design and the dimensions of the product’s semantics to activate the affective memory in the conception of the tablecloth. Qualitative and descriptive research was chosen to obtain theoretical data. The results suggest applying Jordan’s (1999) contributions to the design methodology, bringing the emotional benefits that give pleasure during the use of Norman’s (2004) contributions, which link emotions to three levels of brain processing: visceral (does the user to feel), behavioral (helps the user to do) and reflective (says about the user), as well as the application of semantics bringing to the product the pragmatic dimension and the emotional dimension, creating syntactic elements that have the ability evoke meanings emotions in the minds of consumers.